The Incidence of and Risk Factors for Localized Pain at the Epidural Insertion Site After Epidural Anesthesia: A Prospective Survey of More Than 5000 Cases in Nonobstetric Surgery - Kang X; Zhu Y; Lin K; Xie L; Wen H; Geng W; Zhu S (Dove Medical Press, 2021)
Xianhui Kang,1,* Yeke Zhu,1,* Kun Lin,1 Liwei Xie,1 Heng Wen,1 Wujun Geng,2 Shengmei Zhu1 1Department of Anesthesiology, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Anesthesiology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shengmei ZhuDepartment of Anesthesiology, The First Affiliated Hospital, College of Medicine, Zhejiang University, No. 79 Qingchun Road, Hangzhou, Zhejiang, People’s Republic of ChinaTel +86-571-87236169Fax +86-21-57643271Email smzhu20088@zju.edu.cnWujun GengDepartment of Anesthesiology, The First Affiliated Hospital of Wenzhou Medical University, Nanbaixiang, Ouhai District, Wenzhou City, 325000, Zhejiang Province, People’s Republic of ChinaTel/Fax +86-577-88581162Email gengwujun@126.comBackground: This prospective research aimed to determine the incidence of and risk factors for localized pain at the epidural insertion site following nonobstetric surgery performed with epidural anesthesia.Methods: A total of 5083 surgical inpatients at the teaching hospital undergoing epidural anesthesia were included in the study. The characteristics of the patients, preoperative basic diseases, details of the epidural techniques, surgical procedures and complications were recorded pre-anesthesia until the complications resolved. Multivariate logistic regression analysis was performed to identify predictors of localized pain at the epidural insertion site.Results: In our analysis, target complications were reported in 532 (10.5%) patients; localized pain at the epidural insertion site occurred in 460 (9.05%) patients, while other major complications occurred in 72 (1.45%) patients. A total of 334 patients had mild pain, and 126 patients had moderate pain. The incidence of localized pain at the epidural insertion site was highest among all complications, and the identified risk factors in the multivariate analysis were as follows: lumbar insertion (odds ratio, 1.77; 95% CI 1.33– 2.35), age less than 50 years old (odds ratio, 1.56; 95% CI 1.29– 1.89), multiple block attempts (odds ratio, 3.39; 95% CI 2.68– 4.31), and postoperative patient-controlled epidural analgesia (odds ratio, 0.46; 95% CI 0.33– 0.63).Conclusion: Localized pain at the epidural insertion site is the most common complaint after epidural anesthesia and requires adequate clinical attention. Improving the proficiency of anesthesiologists to avoid repeated punctures is the best way to reduce injuries.Keywords: anesthesia, epidural, localized pain, epidural insertion site, postoperative complications